Estudo termodinâmico da injeção conjunta de surfactante (não-iônico: série de igepal’s) e álcool, com CO 2 como gás carreador: determinação das condições de operação e modelagem dos estados de equilíbrio. - Costa, Moacir Frutuoso Leal da (2024)
Although thermodynamic properties are essential for production and equipment design in oil and gas industries, there is still a lack of experimental data, mainly because of hazardous conditions. Surfactants are compounds with an enormous scope of applications, with the focus in the oil and gas industry being the improvement of the recovered oil from the reservoir. The use of short chain alcohols to increase stability at high temperatures is necessary for such purpose. Keeping that in mind, this work aims to determine the volumetric properties of three nonionic alkyl ethoxylated surfactants (IGEPAL CO-720, CO-630, and CO-520) + methanol binary systems. The carbon dioxide (CO2) solubility on pure surfactants (IGEPAL CO-720 and CO-630) and on the binary mixture IGEPAL CO-720 + methanol was measured. and the thermodynamic modeling through the PC-SAFT equation of state were also provided. Density measurements were carried out in temperatures from 313.15 K to 413.15 K and pressures up to 100.0 MPa. Carbon dioxide (CO2) solubility was evaluated in molar compositions up to 99.9 % of CO2 in the same temperature range. Density data showed regular liquid behavior for pure compounds (surfactant and methanol) and their binary mixtures, with a volume contraction for the surfactants + methanol systems. From the volumetric data, the PC-SAFT equation of state parameters was regressed for the three nonionic surfactants. Surfactant + CO2 equilibrium data parameters were obtained from the density data and provided a maximum %AARD of 15.01 % for the bubble point prediction. Temperature dependent binary interaction parameters were used to implement the bubble point estimation for the ternary mixture IGEPAL CO-720 + methanol + CO2 with an %AARD of 12.60 %. The systems disposed in this work have great industrial interest and a wide range of applications, as well the new set of parameters obtained allow for the prediction of several properties that could be of interest.